Use of The Three-Step Interview Technique in Teaching ESL Speaking - Nurul Kamaliah (English Education Journal, 2018)
The objectives of this study were to examine: (1) Whether there will be a significant difference in speaking achievements between year 11 students taught ESL speaking using the Three-Step Interview technique and those taught through the teacher-centered approach. (2) What will be the response of the students  taught ESL speaking using the Three-Step Interview technique towards it’s use. This study, using an experimental study method, was done with second year (year 11) students at MAS Tgk. Chiek Oemar Diyan, Indrapuri, Aceh Besar District in the academic year 2016/2017. The sample for the research was two classes; XIIPA2 was the experimental class (EG)and XIIPA1 was the control class (CG). The sampling technique used was random sampling. The data was collected from speaking tests and a questionnaire. The data were analyzed by using the t-test for the speaking tests and percentage analysis for the questionnaire. After the treatment ,the results from the data analysis showed that: (1) The Three-Step Interview technique was more effective than the teacher-centered approach for teaching ESL speaking, this was proven by the result from the t-test, in which tcount (3.41) was higher than ttable (2.00); (2) the EG students concerned had quite a positive response (81%) toward the use of the Three-Step Interview technique for use in their speaking class. Therefore, it can be concluded that the Three-step Interview technique effectively improved the students’ achievements in ESL speaking skills as well as providing many other benefits for the students.